The Amsterdam petunia germplasm collection: A tool in plant science - Strazzer, Pamela; Verbree, Bets; Bliek, Mattijs; Koes, Ronald; Quattrocchio, Francesca M. (Frontiers in Plant Science, 2023)
Petunia hybrida has grown to a plant model system used by many researchers to approach a broad range of biological questions. One of the reasons for the success of this organism as lab model are the numerous mutants in the most diverse processes and the still increasing dimension of this collection thanks to a highly active and efficient transposon system. We report here about the origin of the petunia-based research, and we describe the collection of petunia lines that is homed in the University of Amsterdam, where most of the existing genotypes are maintained.